Hubungan Citra Sekolah, Pelayanan Prima, Harapan Orangtua, dan Rasa Bangga Orangtua dengan Keputusan Orangtua Menentukan Sekolah untuk Anaknya - Anis Kurliyatin; Ibrahim Bafadal; Wildan Zulkarnain (Faculty of Education Universitas Negeri Malang, 2017)
Abstract: This study aims to determine the direct and indirect relationships between school image variables, excellent service, parents’ expectations, parents’ pride and parental decisions. This research uses correlational descriptive approach with path analysis technique. The results of the analysis show that: (1) there is no correlation between school image and parents decision through excellent service; (2) there is a relationship between school image and parents decision through parents’ expectation; (3) no relationship between school image and parents’ decision through parents’ pride; (4) there is a relationship between excellent service and parental decisions through parental expectations; (5) there is no relationship between excellent service and parental decisions through parental pride; and (6) there is a relationship between parent's expectation and parental decisions through parents’ pride. Abstrak: Penelitian ini bertujuan untuk mengetahui hubungan langsung dan tidak langsung variabel citra sekolah, pelayanan prima, harapan orangtua, rasa bangga orangtua terhadap keputusan orangtua. Penelitian ini menggunakan pendekatan deskriptif korelasional dengan teknik analisis jalur. Hasil analisis menunjukkan: (1) tidak terdapat hubungan citra sekolah dengan keputusan orangtua melalui pelayanan prima; (2) terdapat hubungan citra sekolah dengan keputusan orangtua melalui harapan orangtua; (3) tidak terdapat hubungan citra sekolah dengan keputusan orangtua melalui rasa bangga orangtua; (4) terdapat hubungan pelayanan prima dengan keputusan orangtua melalui harapan orangtua; (5) tidak terdapat hubungan pelayanan prima dengan keputusan orangtua melalui rasa bangga orangtua; dan (6) terdapat hubungan harapan orangtua dengan keputusan orangtua melalui rasa bangga orangtua.